Prophetic Educational Leadership for Equity and Sustainability: Reconstructing College Governance in The ESG Framework - Taufiq, Taufiq Rahmat; Nuhrodin, Nuhrodin; Ardiansyah, Iwan (Program Studi Manajemen, Universitas Al Ghifari, 2024)
The global challenges of ethical crises, social inequality, and environmental degradation have significantly impacted higher education institutions. Amid growing demands for the implementation of the Environmental, Social, and Governance (ESG) framework, leadership in universities remains largely technocratic and managerial, often neglecting moral and spiritual values. This article aims to formulate a prophetic leadership model within the context of ESG-based sustainable governance. The study employs a qualitative-conceptual approach through library research and interdisciplinary theoretical synthesis, drawing from literature in educational management, business ethics, ESG, and prophetic leadership studies.The proposed model integrates three core elements: (1) prophetic values encompassing justice, trustworthiness, transformation, and humanity; (2) ESG principles, including energy efficiency, social equity, and transparent governance; and (3) implementation domains in higher education, particularly curriculum development, organisational structure, and institutional policy. The findings suggest that incorporating prophetic values into the ESG framework offers significant potential to address the ethical void in contemporary higher education governance.The practical implications of this model open up avenues for leadership reform grounded in spirituality, while promoting the integration of humanistic and sustainability values into academic policy. Future research is recommended to empirically validate the model through both qualitative and quantitative approaches across diverse institutional contexts.